Schmidek and sweet: operative neurosurgical techniques - Quinones-Hinojosa, Alfredo (Philadelphia Elsevier, 2012)
"This book provides the working neurosurgeon with information that would be useful when taking a patient to the operating room. The chapters provide an overview of the topic, a discussion of available options, and results"--
Volume 2.
Keywords: Nervous system-surgery